Analisis Peran Komite Sekolah/Madrasah di SMP/MTs Sekecamatan Namlea Kabupaten Buru - Safira Hasanah Aulia Ode; Jantje E. Lekatompessy (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
This study aims to describe the role of school committees in supporting educational governance in Namlea District, Buru Regency. The focus of the research includes four main functions of the committee: advisory, supportive, supervisory, and mediating roles. A qualitative approach was employed using a case study method at three educational institutions with different backgrounds, namely a public junior high school, a private junior high school, and a private Islamic school (madrasah). Data collection techniques involved in-depth interviews, observation, and documentation. The findings show that the effectiveness of the committee's role is strongly influenced by the openness of school leadership and the intensity of communication with the community. Committees in participatory schools played strategic roles in decision-making, voluntarily supporting school activities, and monitoring programs and student behavior. Conversely, in schools with limited communication, committee roles tended to be passive and administrative. As mediators, committees served to bridge the interests of parents, the community, and the school in fostering mutual understanding